FACTORS INFLUENCING ECONOMIC GROWTH IN LAMPUNG PROVINCE DURING THE COVID-19 PANDEMIC ARE MODERATED WITH THE HUMAN GROWTH INDEX - Fitri Yanti; Safia Maulida; Suharto Suharto; Teguh Setiawan Wibowo; Neneng Hidayat (Jurnal Ekonomi, 2023)
Lampung province, which consists of 15 regencies/cities, is one of the provinces that has the fastest economic growth to recover during Covid-19. Therefore, researchers have a very high curiosity about what factors have influenced Lampung's economic growth in the last 5 years, especially in the year the Covid-19 pandemic occurred.